Response to Article “Autophagy Inhibits Inflammation via Down-Regulation of p38 MAPK/mTOR Signaling Cascade in Endothelial Cells” [Letter] - Maha MS; Panjaitan NSD (Dove Medical Press, 2023)
Masri Sembiring Maha, Novaria Sari Dewi Panjaitan Center for Biomedical Research, Research Organization for Health, National Research and Innovation Agency (BRIN), Cibinong Science Center, Cibinong, West Java, IndonesiaCorrespondence: Novaria Sari Dewi Panjaitan, Center for Biomedical Research, Research Organization for Health, National Research and Innovation Agency (BRIN), Cibinong Science Center, Jl. Raya Bogor No. 490, Cibinong – Bogor Km. 46, Cibinong, West Java, Indonesia, Email nova014@brin.go.id